2016
DOI: 10.1016/j.neuroimage.2016.06.055
|View full text |Cite
|
Sign up to set email alerts
|

Temporo-parietal connectivity uniquely predicts reading change from childhood to adolescence

Abstract: Previous research has shown that left posterior middle temporal gyrus (pMTG) is a core node in the semantic network, and cross-sectional studies have shown that activation in this region changes developmentally and is related to skill measured concurrently. However, it is not known how functional connectivity with this region changes developmentally, and whether functional connectivity is related to future gains in reading. We conducted a longitudinal functional magnetic resonance imaging (fMRI) study in 30 ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 77 publications
(101 reference statements)
0
19
0
2
Order By: Relevance
“…Much of this research has focused on behavioral predictors, such as performance on various standardized measures. However, researchers within the last few decades have begun to extend this work by exploring the use of language-related brain-based predictors (e.g., Lee et al, 2016;Linkersdorfer et al, 2014;McNorgan et al, 2011;Preston et al, 2016;Smith et al, 2018). A subset of this research, which has examined the use of both behavioral and neural predictors, has shown that both functional-and structural-based neural measures explain unique variance in reading growth over that of purely behavioral measures (e.g., Bach et al, 2013;Hoeft et al, 2007;Hoeft et al, 2011;Maurer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Much of this research has focused on behavioral predictors, such as performance on various standardized measures. However, researchers within the last few decades have begun to extend this work by exploring the use of language-related brain-based predictors (e.g., Lee et al, 2016;Linkersdorfer et al, 2014;McNorgan et al, 2011;Preston et al, 2016;Smith et al, 2018). A subset of this research, which has examined the use of both behavioral and neural predictors, has shown that both functional-and structural-based neural measures explain unique variance in reading growth over that of purely behavioral measures (e.g., Bach et al, 2013;Hoeft et al, 2007;Hoeft et al, 2011;Maurer et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In order to make direct links to cognition and test-specific hypotheses arising from the IS model of brain development, longitudinal task-based fMRI studies are critically needed. There have only been six longitudinal developmental fMRI studies of task-related activation, [16][17][18][19][20] with only one study examining changes in brain connectivity. 21 Furthermore, extant studies of growth trajectories using longitudinal designs have focused on regional changes in brain response.…”
Section: Introductionmentioning
confidence: 99%
“…Traditional functional connectivity analysis focusing only on seed regions (e.g., VWFA and IFG in the aforementioned studies) fails to give a complete picture of brain connectivity profiles. The seed regions selected in most previous studies on reading development are mainly located in the left hemisphere (Bitan, ; Bitan et al, ; Lee et al, ) or in classic cortical regions for reading (Koyama et al, ). However, numerous studies (Banai et al, ; Liu et al, ; Price, ) have found that reading also involves regions beyond the left‐lateralized classic reading network, such as limbic and subcortical regions (Banai et al, ; Hornickel, Skoe, Nicol, Zecker, & Kraus, ), low‐level visual perception regions (Liu et al, ; Price, ; Sun, Yang, Desroches, Liu, & Peng, ), and high‐level executive function regions (Lee et al, ; Price, ; Whitney, Jefferies, & Kircher, ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent longitudinal study investigated how the functional connectivity of the left posterior middle temporal gyrus (pMTG) in a visual semantic judgment task changed over development. It revealed longitudinal increases in functional connectivity between the pMTG and the inferior parietal lobule (IPL) for weak semantic association word pairs and suggested that early development of semantic representations may be facilitated by enhanced engagement of phonological short‐term memory (Lee, Booth, & Chou, ).…”
Section: Introductionmentioning
confidence: 99%